The current role of staging laparoscopy for patients with radiographically resectable pancreatic adenocarcinoma - Yamashita, Yo-ichi; Baba, Hideo (Laparoscopic Surgery, 2018)
We read with great interest the paper recently published in the Annals of Surgical Oncology entitled “Reappraisal of Staging Laparoscopy for Patients with Pancreatic Adenocarcinoma (PDAC): A Contemporary Analysis of 1001 Patients” written by Fong et al. of Harvard Medical School (1).